Reduced lower extremity vibratory perception in osteoarthritis of the knee - Shakoor, Najia; Agrawal, Alan; Block, Joel A. (Arthritis and rheumatism, 2008)
Objective Vibratory perception threshold (VPT) assesses a distinct yet related sensory pathway that has been associated with neuropathic arthropathy but has not been assessed in knee osteoarthritis (OA). The purpose of this study was to evaluate VPT in subjects with knee OA to determine whether the lower extremity afferent deficits observed in knee OA involve more than just proprioception. Methods Twenty‐seven individuals with symptomatic and radiographic knee OA were compared with 14 age‐matched normal subjects. VPT was assessed using a biothesiometer. Five sites of the lower extremity were evaluated. VPT of OA subjects was compared with VPT of normal subjects. Results VPT of the OA subjects was significantly reduced at all 5 testing sites compared with normal subjects (P < 0.05 at all sites). VPT scores (mean ± SEM volts) for OA subjects and normal subjects were as follows: first metatarsophalangeal joint (15.0 ± 1.9 versus 6.4 ± 0.9), medial malleolus (22.0 ± 2.2 versus 12.3 ± 1.4), lateral malleolus (22.3 ± 2.0 versus 10.4 ± 0.8), medial femoral condyle (25.8 ± 1.8 versus 15.9 ± 1.9), and lateral femoral condyle (27 ± 1.9 versus 18.9 ± 2.4). Conclusion This was the first study to evaluate VPT in OA and demonstrate that VPT is reduced at the lower extremity of subjects with knee OA. The noted deficits in VPT may have significant implications in the neuromechanical pathophysiology of OA. VPT is a simple and reliable technique to measure sensory deficits in subjects with OA of the knee.